2017
DOI: 10.1128/aac.02280-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antifungal Profile of a Novel and Long-Acting Inhaled Azole, PC945, on Aspergillus fumigatus Infection

Abstract: The profile of PC945, a novel triazole antifungal designed for administration via inhalation, was assessed in a range of in vitro and in vivo studies. PC945 was characterized as a potent, tightly binding inhibitor of Aspergillus fumigatus sterol 14α-demethylase (CYP51A and CYP51B) activity (50% inhibitory concentrations [IC50s], 0.23 μM and 0.22 μM, respectively) with characteristic type II azole binding spectra. Against 96 clinically isolated A. fumigatus strains, the MIC values of PC945 ranged from 0.032 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 37 publications
3
88
0
1
Order By: Relevance
“…This superior profile probably arises from several factors, including pharmacokinetics, physicochemical properties and unique pharmacological characteristics. As reported earlier, PC945 has been demonstrated to have a longer duration of action in bronchial epithelial cells and hyphae than voriconazole (29). Moreover, the molecule is retained within the lung, resulting in low systemic exposure after oral and face mask nebulization in a phase 1 study (NCT02715570) (40) (in preparation).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This superior profile probably arises from several factors, including pharmacokinetics, physicochemical properties and unique pharmacological characteristics. As reported earlier, PC945 has been demonstrated to have a longer duration of action in bronchial epithelial cells and hyphae than voriconazole (29). Moreover, the molecule is retained within the lung, resulting in low systemic exposure after oral and face mask nebulization in a phase 1 study (NCT02715570) (40) (in preparation).…”
Section: Discussionmentioning
confidence: 86%
“…binding (29,30). PC945 has been shown to have potent in vitro and in vivo antifungal activity on A. fumigatus isolates with inhibition of the enzyme lanosterol 14α-demethylase (CYP51A1) and also demonstrated that topical once daily treatment of PC945 was highly effective versus fungal burden in lung tissue and several biomarkers (galactomannan, cytokines) in serum and bronchoalveolar lavage fluid (BALF) in temporarily neutropenic mice infected with A. fumigatus when compared with intranasally treated posaconazole and voriconazole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore difficult to interpret the different effects of two administration routes, although we found that both oral and intranasal treatment improved survival proportions similarly. However, we carefully optimised the intranasal volume (35 μL), and as previously reported, 19 35 μL of intranasal volume is expected for 60% of inoculum to deposit in lung. This means 40% of inoculum or treated posaconazole might be swallowed or stayed in nasal cavity, and therefore it cannot be ruled out that intranasally treated posaconazole was exposed systemically via gastrointestinal route or nasal route.…”
Section: Discussionmentioning
confidence: 99%
“…On the day of infection, spore counts were assessed by haemocytometer and the inoculum was adjusted to obtain a concentration of 1.67 × 10 8 spores mL −1 of physiological saline. To induce immunosuppression and neutropenia, A/J mice were dosed with hydrocortisone (Sigma H4881; 125 mg/kg, sc) on days 3, 2 and 1 before infection, and with cyclophosphamide (Sigma C0768; 250 mg/kg, ip) 2 days before infection as previously reported . On day 0, animals were infected with the spore suspension (30 μL, intranasally 15 μL into each nostril) under anaesthesia with 3% isoflurane.…”
Section: Methodsmentioning
confidence: 99%